The book's shape: imagine the ‘classics’ of 20th Century (Prassi Ecdotiche della Modernità Letteraria, 2017)
This paper examines the structure of some ‘classics’ books of 20th Century Literature employing the Warburghian iconology method. Books, in fact, combine a concrete object with visual, textual and paratextual elements (visual and verbal) joined in a whole that is both an aesthetic and a communicative object.
Keywords: book's shape; ebook; epub; editions; publishing